BIOLOGICAL ACTIVITIES OF POLYGONUM BARBATUM - Chaudhry, Bashir Ahmad; Syad, Muhammad Younas; Janbaz, Khalid Hussain; Dasti, Altaf Ahmad; Loothar, Bashir Ahmad (Journal of Research (Science), 2003)
In continuation of our screening programme for biological activities of the higher plants, we have studied Polygonum barbatum. The aerial parts of this species were extracted successively with dichloromethane and methanol. Extracts were submitted to a battery of biological tests including cholinergic activity, spasmolytic activity, larvicidal activity, brine shrimp toxicity, antifungal and antibacterial activities. Dichloromethane extract showed brine shrimp toxicity and spasmolytic activity whereas the methanol extract was found to possess cholinergic activity.